Penerapan Activity-Based Costing dalam Berbagai Industri: Analisis Bibliometrik pada Publikasi Ilmiah - Mubaroq, Afiq Chamim; Setyorini, Christina Tri (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2024)
Purpose: This research uses bibliometric analysis methods with the aim of determining trends in the application of activity-based costing in various industries. Method: The data used comes from articles published on Scopus and Google Scholar with a time span of 1980 to 2023. The number of articles produced was 1,180 and selected according to the topic of discussion, resulting in 946 articles used as research data. Researchers use several software programs in research, such as Publish or Perish to obtain research data, Mendeley and Excel to help select data, and VOS viewer to process research data. Results: The research results showed that there were 946 scientific papers that generated 58,915 citations; in addition, there were several researchers, journals, and publishers that were influential in activity-based costing research. The bibliometric map produces five clusters of different importance. Implications: Theoretically, the results of this research provide a more in-depth view of research trends regarding the application of activity-based costing in various types of industries. Apart from that, practically, organizations or companies can use it as a consideration in determining their policies, especially those related to organizational activities and the implementation of activity-based costing. Novelty: This research discusses in depth research trends in activity-based costing, especially topics related to technological advances and corporate awareness of the environment and sustainability, this will have an impact on ABC research. Not many studies have discussed this topic using bibliometric analysis methods.